Endoscopic full-thickness resection of gastric and duodenal subepithelial lesions using a new, flat-based over-the-scope clip - Kappelle, Wouter F. W. (Surg Endosc, 2017)
BACKGROUND: Surgical resection of upper gastrointestinal (GI) subepithelial tumors (SETs) is associated with significant morbidity and mortality. A new over-the-scope (OTS) clip can be used for endoscopic full-thickness resection (eFTR). We aimed to prospectively evaluate feasibility and safety of upper GI eFTR with a new, flat-based OTS clip. METHODS: Consecutive patients with a gastric or duodenal SET < 20 mm were prospectively included. After identification of the lesion, the clip was placed and lesions were resected. Patients were followed for 1 month to assess severe adverse events (SAEs); 3–6 months after eFTR, endoscopy was performed. RESULTS: eFTR was performed on 13 lesions in 12 patients: 7 gastric and 6 duodenal SETs. Technical success was achieved in 11 cases (85%). In all 11 cases, R0-resection was achieved. In all 6 duodenal cases and in one gastric case, FTR was achieved (64%). One SAE (pain) was observed after eFTR of a gastric SET. After eFTR of duodenal SETs, several SAEs were observed: perforation (n = 1), microperforation (n = 3), and hemorrhage (n = 1). During follow-up endoscopy, the clip was no longer in situ in most patients (7 of 10; 70%). CONCLUSIONS: eFTR with this new flat-based OTS clip is feasible and effective. Although gastric eFTR was safe, eFTR in the duodenum was complicated by (micro)perforation in several patients. Therefore, the design of the clip or the technique of resection needs further refinement to improve safety of resection of SET in thin-walled areas such as the duodenum before being applied in clinical practice. Dutch trial register: NTR5023. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00464-017-5989-8) contains supplementary material, which is available to authorized users.